Sistemas de preparo de solos de cerrado: efeitos nas propriedades físicas e na cultura do milho - Centurion, J. F.; Dematte, JLI (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 1992)
The purpose of this work was to assess the effects of soil preparation methods (with or without subsoiling) on physical properties of a cerrado soil cropped to corn during the, 1986/87 season, in the Selviria county (Mato Grosso do Sul, Brazil). Also, the objective of this was to check the changes in the soil (dark red latosol-Acrustox) caused by the preparation after nine years of cultivation in comparison with natural state. The experiment consisted of six soil preparation systems: conventional, superpreparation, reversed, revolving hoe, reduced and no-tillage. Along with these systems subsoiling was also tested. The reversed system showed the best com grain yield. Subsoiling only presented positive results in productivity with the no-tillage system. All the preparation system tested degraded the physical properties in comparison with the natural soil.

O objetivo deste trabalho foi avaliar os efeitos de sistemas de preparo do solo (submetidos ou não à subsolagem) nas propriedades físicas de um solo sob cerrado, cultivado com milho, no ano agrícola de 1986/87, no município de Selvíria, MS. Observaram-se também as alterações ocasionadas pelo manejo desse solo (Latossolo Vermelho-Escuro, argiloso) após nove anos de cultivo, em relação ao seu estado natural. O experimento constou de seis sistemas de preparo do solo: convencional, superpreparo, invertido, enxada rotativa, reduzido e semeadura direta. Aliada a tais sistemas testou-se a subsolagem. O sistema invertido de preparo proporcionou um melhor rendimento de grãos de milho, ao passo que a semeadura direta apresentou os menores rendimentos. A subsolagem só surtiu efeito em termos de produtividade no sistema de semeadura direta. Todas as formas de preparo degradaram as propriedades físicas do solo em relação ao seu estado natural.
Effects of preparation systems on the physical-properties and on the corn crop in a soil under cerrado vegetation
Keywords: Soil management; Zea mays